Practically joking - Marsh, Moira 1958- (Utah State University Press, 2015)
"In Practically Joking, the first full-length study of the practical joke, Moira Marsh examines the value, artistry, and social significance of this ancient and pervasive form of vernacular art. Though it is sometimes dismissed as the lowest form of humor, the practical joke comes from a lively tradition of expressive play. Both sophistication and intellectual satisfaction is found in them, and the best demand significant skill and talent, not only to think up but also to execute. Practically Joking establishes the practical joke as an art form subject to critical evaluation by both practitioners and audiences, operating under the guidance of local aesthetic and ethical canons. Marsh studies the range of genres that pranks comprise, offers a theoretical look at the reception of practical jokes based on "transgressive humor," a theory that sees humor as playful violation, and uses real life examples of practical jokes in context to establish the form's varieties and meanings as an independent genre, as well as its inextricable relationship with a range of folklore forms. Scholars of folklore, humor and popular culture will find much of interest in Practically Joking"..